Patriotic trends in the poems of Mahmoud Sami Al-Baroudi: A Descriptive and Analytical Study - Mohammed Hafees Mohammed Shareef; Nasr El Din Ibrahim Ahmed Hussain (Indonesian Journal of Arabic Studies, 2022)
Abstract: The poet Mahmoud Sami Al-Baroudi is considered a pioneer of the modern literary renaissance; where he renewed the style of poetry, relying on the molds of the ancients in style and formulation, pouring meanings from his personal experiences and the issues occurred on his time. Among the manifestations of renewal in his poetic productions are the patriotic poems he composed through which he was able to highlight his Egyptian patriotic sentiment. Since some critics directed the poet into questioning his Egyptian patriotism, and that he did not record in his poetic traces of the issues and topics of his time, this study came with the aim of shedding light on his national trends and the factors affecting his Egyptian patriotism, and the main themes in which he dealt with the issues of his time revealing his patriotism sincere. This study is important because it focuses on patriotic poems that clearly effect on the feelings; Considering that national literature has a significant impact on the formation of a good citizen, The study concluded that the patriotic trend changed in al-Baroudi’s poems according to the different stages he went through in his life, and several factors combined to refine his national personality, which led to the expansion of the circle of patriotic poetry as he invested his poetic output in resisting political corruption, urging Egyptians to renaissance education, establishing the constitution and parliament, praising Egyptian heroes, and fighting against the foreign colonialism, as well as providing guidance to Egypt’s rulers.